2005
DOI: 10.1111/j.1365-2389.2005.00688.x
|View full text |Cite
|
Sign up to set email alerts
|

Light penetration in soil and particulate minerals

Abstract: Knowledge of light penetration in soils is of particular interest for photolytic degradation of pesticides, for laser-induced fluorescence spectroscopy and remote sensing, and for understanding better the germination of seeds. To date little information has been available in the literature on this topic. In this paper light penetration in soils is determined successfully using diffuse reflectance and transmittance spectroscopy and the relatively simple Kubelka-Munk model. Using the latter model of light propag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
95
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(97 citation statements)
references
References 28 publications
2
95
0
Order By: Relevance
“…Anyway, Atkinson and Arey (2003) give a very detailed overview on physical-chemical degradation of VOCs in the atmosphere where photolysis and spontaneous reactions with OH radicals (under the presence of light), NO 3 radicals (under the absence of light), O 3 (under the presence of light), and Cl atoms (at coastlines) are the main processes responsible for abiotic VOC degradation. Considering the fact that light can only reach habitats located in the soil surface (Woolley and Stoller 1977;Ciani et al 2005), photolysis and other lightdriven reactions (with OH radicals and O 3 ) only occur in a thin surface zone (Konstantinou et al 2001). In this zone, OH radicals and O 3 are produced by microorganisms or they diffuse from the atmosphere.…”
Section: Physical-chemical Degradation Of Vocsmentioning
confidence: 99%
“…Anyway, Atkinson and Arey (2003) give a very detailed overview on physical-chemical degradation of VOCs in the atmosphere where photolysis and spontaneous reactions with OH radicals (under the presence of light), NO 3 radicals (under the absence of light), O 3 (under the presence of light), and Cl atoms (at coastlines) are the main processes responsible for abiotic VOC degradation. Considering the fact that light can only reach habitats located in the soil surface (Woolley and Stoller 1977;Ciani et al 2005), photolysis and other lightdriven reactions (with OH radicals and O 3 ) only occur in a thin surface zone (Konstantinou et al 2001). In this zone, OH radicals and O 3 are produced by microorganisms or they diffuse from the atmosphere.…”
Section: Physical-chemical Degradation Of Vocsmentioning
confidence: 99%
“…To date, several microorganisms have been identified that are capable of anaerobic Fe (II) oxidation (Bruce et al 1999;Chaudhuri et al 2001;Edwards et al 2003;Finneran et al 2002;Hafenbradl et al 1996;Lack et al 2002a;Straub et al 1996;Straub et al 1999;Widdel et al 1993), however, few of these grow by the metabolism (Weber et al 2006a). Given that light penetration of soil and particulate matter is only between 8 to 200μm (Ciania et al 2005), light independent reactions such as nitrate-dependent Fe(II) oxidation are more likely to dominate bio-oxidative processes in saturated and subsurface soil/sedimentary environments.…”
Section: Introductionmentioning
confidence: 99%
“…Light very rapidly declines in soil, with less than 99% of light remaining after one mm (Ciani et al, 2005). Light penetrates farther in leaf litter, and its decline follows the Beer-Lambert law (Facelli & Pickett, 1991): where RI is relative illuminance, b is transmittance constant of litter, and M is the amount of litter per g/m 2 .…”
Section: Introductionmentioning
confidence: 99%